Synthesis, properties and biological potential some condensed derivatives 1,2,4-triazole - Gotsulya, A. S.; Zaika, Y.; Brytanova, T. S.; Гоцуля, Андрій Сергійович; Британова, Тетяна Сергіївна (My University, 2022)
Objective: The aim of the work was to develop effective methods for the synthesis of biologically active heterocyclic systems containing pyrrole, indole and 1,2,4-triazole. In this study, firstly fourteen [1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles compounds requiring for this study were synthesized. Material and Method: Chemical structures of synthesized compounds were characterized with elemental analysis, 1H NMR, LC-MS techniques. The biological potential of the synthesized substances was estimated by the molecular docking method. Result and Discussion: An optimal method for the synthesis of [1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles has been developed. In molecular modeling studies, the compounds were found to be similar to known drugs in some respects. Besides, the interaction of each molecule in the active site of the crystal structures of cyclooxygenase-1, lanosterol 14-α-demethylase, kinases of anaplastic lymphoma were considered as in silico.
Gotsulya A. - https://orcid.org/0000-0001-9696-221X; Britanova T. - https://orcid.org/0000-0003-1805-4552.
Keywords: Docking; indole; pyrrole; synthesis; 1,2,4-triazole